Cardiovascular effects of training for a marathon run in unfit middle aged men. Issue 6597 (29th August 1987) - Findlay, I N; Taylor, R S; Dargie, H J; Grant, S; Pettigrew, A R; Wilson, J T; Aitchison, T; Cleland, J G; Elliott, A T; Fisher, B M
Abstract : The effects of a 30 week exercise programme on serum lipid values, blood pressure, and cardiac function were assessed in a group of sedentary men aged 35-50 training for their first marathon. Mean serum cholesterol concentration (n = 33) fell by 12% from 6.54 (SE 0.18) to 5.76 (0.15) mmol/l (mean fall 0.78 mmol/l; 95% confidence interval 0.52 to 1.04 mmol/l), serum triglyceride concentration (n = 33) by 22% from 1.56 (0.17) to 1.21 (0.09) mmol/l (mean fall 0.34 mmol/l; 95% confidence interval 0.12 to 0.56 mmol/l), and mean blood pressure (n = 27) by 10% from 102 (2) to 92 (2) mm Hg (mean fall 10 mm Hg; 95% confidence interval 7 to 13 mm Hg). These changes were not explained by changes in body composition. Peak exercise left ventricular end diastolic volume (n = 16) increased with training; as a result of this and an increased exercise left ventricular ejection fraction peak exercise cardiac output increased from 19.9 (1.2) to 23.1 (3.0) l/min (mean rise 3.2 l/min; 95% confidence interval 1.5 to 5.0 l/min). Maximum oxygen consumption increased from 33.9 (1.6) to 39.0 (1.3) ml/kg/min (mean rise 5.0 ml/kg/min; 95% confidence interval 1.8 to 8.2 ml/kg/min). This study showed favourable effects on coronary risk factors and cardiac function and supports the place of regular exercise in coronary prevention programmes.